Microscopic Theory for Spontaneous Fission - Sadhukhan, Jhilam (Frontiers in Physics, 2020)
Nuclear fission is a fascinating field of research that involves large-amplitude collective dynamics of a microscopic many-body system. Specifically, the process of spontaneous-fission decay can only be explained within the quantum tunneling phenomenon. The present review discusses recent advancements in the theoretical understanding of spontaneous fission. These concern precise prediction of the spontaneous fission observables like fission lifetime and distribution of fragment yields. The theoretical developments presented here are based on a coherent coupling between the adiabatic collective dynamics and the static inputs obtained from the nuclear energy density functional formalism.